Properties of Thermal Conductivity According to Replacement Ratio of Paper Ash of Lightweight Composite Panel Core - Jong Kim, Won; jeong Pyeon, Su; Soo Lee, Sang (International Journal of Engineering and Technology, 2018)
Background/Objectives: Korea, which is mostly composed of multi-family houses, is paying attention to the importance of sound insulation, insulation, and fireproofing in the environment of multi-family housing.Methods/Statistical analysis: This study is a study on the production of lightweight composite panel core using inorganic by-product, blast furnace slag, paper ash, polysilicon sludge and vermiculite. When the paste is lightweight due to the foamability of the paper ash, the applicability of the paste as a building dry panel is examined.Findings:As a result of the analysis of the experimental results, the fluidity shows a tendency to decrease as the replacement rate of the paper ash is increased. The compressive strength shows a tendency to decrease as the substitution rate of paper ash increases and the compressive strength shows a constant tendency with a substitution rate of more than 15%. As the substitution rate of paper ash increases, the size of bubbles on the surface of the cured product increases and the rate of bubble generation increases.Improvements/Applications: As a result of this study, the thermal conductivity decreases as the substitution rate of paper ash increases, and further study is required for the fire resistance test.Â